Unsteady Radiative Maxwell Fluid Flow over an Expanding Sheet with Sodium Alginate Water-Based Copper-Graphene Oxide Hybrid Nanomaterial: An Application to Solar Aircraft. (5th September 2022) - Chandrasekaran, S.; Satyanarayana Gupta, M.; Jangid, Sanju; Loganathan, K.; Deepa, B.; Chaudhary, Dinesh Kumar
Abstract : The primary heat source from the sunlight is solar energy, which is used in photovoltaic panels, solar power plates, photovoltaic streetlights, and solar-based hybrid nanocomposites. A hybrid nanofluid is traversing an expanding sheet in this investigation. Maxwell fluid stream with two nanoparticles is going towards a trough with a parabolic form and is situated within the solar aircraft wing to investigate the phenomena of heat transfer rate. The term solar thermal radiation was introduced to describe heat transfer occurrence. The effectiveness of heat transmission from airplane wings is assessed by taking into account unique phenomena such as magnetic field and heat source. The bvp4c procedure was applied to quantitatively explain the energy and motion equations with MATLAB software. The copper (Cu) and graphene oxide (GO) nanosolid particles are mixed with sodium alginate (SA), a common liquid, to form the nanosolid particles. Numerous control variables are thoroughly examined, including temperature, shear stress, motion, friction component, and Nusselt number. The skin-friction coefficient upsurges with a growing magnetic impression. The upsurge in Deborah number reduces the skin-friction coefficient. The heat source impression declines the heat transport rate but upsurges the skin-friction coefficient. The skin-friction coefficient and heat transport rate increase with growing magnetic impression. When it comes to heat transfer analysis, hybrid nanofluid efficiency is substantially superior to that of regular nanofluid.